2007
DOI: 10.1016/j.cub.2007.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin-Mediated Constitutive Endocytosis of PIN Auxin Efflux Carriers in Arabidopsis

Abstract: Endocytosis is an essential process by which eukaryotic cells internalize exogenous material or regulate signaling at the cell surface [1]. Different endocytic pathways are well established in yeast and animals; prominent among them is clathrin-dependent endocytosis [2, 3]. In plants, endocytosis is poorly defined, and no molecular mechanism for cargo internalization has been demonstrated so far [4, 5], although the internalization of receptor-ligand complexes at the plant plasma membrane has recently been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
678
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(710 citation statements)
references
References 36 publications
30
678
2
Order By: Relevance
“…In these transformant plants, the ap2m mutant phenotype was complemented (described below), suggesting that the AP2M-GFP fusion protein is functional and behaves similarly to its endogenous counterpart. Confocal laser scanning microscopy revealed that, in the root tip cells of AP2M-GFP ap2m plants, the fluorescence of AP2M-GFP colocalized with FM4-64, a fluorescent lipophilic dye that labels the plasma membrane (Ueda et al, 2001;Dhonukshe et al, 2007), and was dispersed throughout the cytosol ( Figure 1A). Colocalization of AP2M-GFP fluorescence with FM4-64 was also observed in the cotyledon epidermal cells of AP2M-GFP ap2m plants (see Supplemental Figure 1 online).…”
Section: Arabidopsis Ap2m Localizes At the Plasma Membrane In A Tyra2mentioning
confidence: 99%
See 1 more Smart Citation
“…In these transformant plants, the ap2m mutant phenotype was complemented (described below), suggesting that the AP2M-GFP fusion protein is functional and behaves similarly to its endogenous counterpart. Confocal laser scanning microscopy revealed that, in the root tip cells of AP2M-GFP ap2m plants, the fluorescence of AP2M-GFP colocalized with FM4-64, a fluorescent lipophilic dye that labels the plasma membrane (Ueda et al, 2001;Dhonukshe et al, 2007), and was dispersed throughout the cytosol ( Figure 1A). Colocalization of AP2M-GFP fluorescence with FM4-64 was also observed in the cotyledon epidermal cells of AP2M-GFP ap2m plants (see Supplemental Figure 1 online).…”
Section: Arabidopsis Ap2m Localizes At the Plasma Membrane In A Tyra2mentioning
confidence: 99%
“…Treatment with TyrA23 inhibits internalization of the PIN-FORMED auxin transporters and the water channel PLASMA MEMBRANE INTRINSIC PROTEIN2 (Dhonukshe et al, 2007), the iron transporter IRON-REGULATED TRANSPORTER1 (Barberon et al, 2011), the plant-specific endocytic SNARE VESICLE-ASSOCIATED MEMBRANE PROTEIN727 (Ebine et al, 2011), and the ligand-activated brassinosteroid receptor BRASSI-NOSTEROID INSENSITIVE1 (Irani et al, 2012). Amino acid substitutions of the YXXF motif eliminate polar localization of the Arabidopsis boron transporter REQUIRES HIGH BORON1 in the plasma membrane of root tip cells (Takano et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…CCPs and CCVs), and the existence of plant homologs of proteins involved in clathrin-mediated endocytosis, suggest that this pathway takes place in plant cells (Low and Chandra, 1994;Holstein, 2002;Murphy et al, 2005). Moreover, clathrin-dependent endocytosis has been shown very recently to be operational in plants and used as a predominant pathway, as in animal cells, for internalization of plasma membrane proteins, such as the auxin carrier PIN1 in Arabidopsis (Arabidopsis thaliana), and for spindle and phragmoplast formation as well as for endocytosis in tobacco (Nicotiana tabacum) Bright Yellow-2 (BY-2) cells (Dhonukshe et al, 2007;Tahara et al, 2007). In addition, endocytosis of the human Tf-R, known to be clathrin-dependent in animal cells, is inhibited by an RME inhibitor after expression in plant protoplasts, suggesting the existence of clathrin machinery for RME in plant cells (Ortiz-Zapater et al, 2006).…”
mentioning
confidence: 99%
“…Earlier it was reported that, maximum of PIN proteins are plasmamembrane localized and present in polarized fashion but are usually non static in nature (Friml and Palme 2002;Zazímalová et al 2010;Viaene et al 2013). They undergoes constitutive recycling between plasmamembrane and endomembrane compartments and can easily re-localize rapidly to various parts of cell by transcytosis in response to different environmental signals Dhonukshe et al 2007;Kleine-Vehn et al 2008). Maximum of OsPILS genes were found to be subcellularly localized either in endoplasmic reticulum and vacuoles (Table 3).…”
Section: Resultsmentioning
confidence: 95%